Erfahrungen mit Lichtfallen für den Warndienst. - Mesch, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1965)
In connection with the warning service against codling moths (Carpocapsa pomonella Linnaeus), studies were made to improve the results of light traps. A slightly modified form of the "Minesota light trap" (fig. 7, 8, 15) was found to be most suitable for our purposes. Mercury vapour lamps of the types HQA 125 W and HQL 250 W, made by VEB Berliner Glühlampenwerk, were used in the light traps. Catches with the HQL 250 W lamp were bigger and could be evaluated more easily. The device shown in fig. 14 proved to effective in collecting the caught insects. It kills them instantly with carbon tetrachloride and thus preserves them intact. The counts registered not only apple moths but all noxious insects that could be easily determined by the operators of the light traps. The best locations and uses of light traps are described.